Mass spectrometry-based identification of new anti-Ly and known antisynthetase autoantibodies. Issue 4 (26th December 2022) - Vulsteke, Jean-Baptiste; Derua, Rita; Dubucquoi, Sylvain; Coutant, Frédéric; Sanges, Sebastien; Goncalves, David; Wuyts, Greet; De Haes, Petra; Blockmans, Daniel; Wuyts, Wim A; Claeys, Kristl G; De Langhe, Ellen; et al.
Abstract : Objectives: To discover new and detect known antisynthetase autoantibodies (ASAs) through protein immunoprecipitation combined with gel-free liquid chromatography-tandem mass spectrometry (IP-MS). Methods: IP-MS was performed using sera of individuals showing features of antisynthetase syndrome (ASyS) without (n=5) and with (n=12) previously detected ASAs, and healthy controls (n=4). New candidate aminoacyl-tRNA-synthetase (ARS) autoantigens identified through unbiased IP-MS were confirmed by IP-western blot. A targeted IP-MS assay for various ASA specificities was developed and validated with sera of patients with known ASAs (n=16), disease controls (n=20) and healthy controls (n=25). The targeted IP-MS assay was applied in an additional cohort of patients with multiple ASyS features or isolated myositis without previously detected ASAs (n=26). Results: Autoantibodies to cytoplasmic cysteinyl-tRNA-synthetase (CARS1) were identified by IP-MS and confirmed by western blot as a new ASA specificity, named anti-Ly, in the serum of a patient with ASyS features. Rare ASAs, such as anti-OJ, anti-Zo and anti-KS, and common ASAs could also be identified by IP-MS. A targeted IP-MS approach for ASA detection was developed and validated. Application of this method in an additional cohort identified an additional patient with anti-OJ autoantibodies that were missed by line and dot immunoassays. Discussion: CARS1 is the dominant cognate ARS autoantigen of the newly discovered anti-Ly ASA specificity. Rare and common ASA specificities could be detected by both unbiased and targeted IP-MS. Unbiased and targeted IP-MS are promising methods for discovery and detection of autoantibodies, especially autoantibodies that target complex autoantigens.